ANALISIS KEADAAN PSIKIS WANITA LANJUT USIA DI PANTI JUMPO " JOYAH UKEN" KECAMATAN BEBESEN KABUPATEN ACEH TENGAH - Annisa Arrumaysah Daulay; Masdiana Masdiana; Ayu Tiara; Rojali Rojali; Ambya Satria Utomo; Fitri Amelia Harahap (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Elderly is a period in the final stage in a person's life. Life in old age or the elderly is vulnerable to changes in psychological conditions. However, in this current study, the researchers focused more on the psychological state of elderly women in terms of the types of "senility and depression" experienced by elderly women at the Joyah Uken Jumpo Home, Bebesen District, Central Aceh District. the purpose of this research is to find out how the psychological condition of elderly women in nursing homes. This study used an equal method, relying on interviews and direct observation by researchers at the Joyah Uken Jumpo Orphanage. and the subject of this research is the researcher himself, and the research object is the elderly women who are in the "joyah uken" jumpo home. The results showed that the psychological condition of elderly women in the joyah uken jumpo home was quite good, but there were several elderly women who experienced psychological disorders in elderly women in joyah, while the solutions and services provided by the puskesmas were therapy, posbindu, gymnastics for the elderly a month twice at the Joyah Uken Jumpo Home, Bebesen District, Central Aceh District